Hubungan Tingkat Perolehan Sumber Informasi Dengan Tingkat Pengetahuan Remaja Tentang HIV/AIDS Di SMK Negeri 1 Pandak Bantul - Adud, Adud; Desi Ekawati; Wiwin Hindriyawati; Anugerah Destia Trisetyaningsih (JURNAL ILMIAH NUSANTARA, 2025)
Data from the Yogyakarta Health Office, the number of new HIV cases increased in 2022, from 327 people to 916 during the 2016-2022 period, there were 2,050 AIDS cases and 6,784 HIV/AIDS cases. Bantul Regency is second only to Sleman Regency with 160 new AIDS cases dominated by the 25-29 year old and 15-19 year old age groups. This study aims to determine the relationship between the level of acquisition of information sources with the level of knowledge of adolescents about HIV/AIDS at SMK Negeri 1 Pandak Bantul. Using quantitative analytic survey method with cross sectional approach. Stratified random sampling technique. The sample size was 90 respondents at SMK Negeri 1 Pandak Bantul. Data were analyzed univariately and bivariately using the Chi-Square test. The results stated that the characteristics of the respondents were mostly 17 years old,39 (43.3%) and dominated by women 75 (83.3%). The majority of respondents' level of information source acquisition was in the good category, 74 (82.2%). The level of knowledge of respondents about HIV/AIDS was in the good category, 83 (92.2%) respondents. The result of the Chi-Square test calculated 1.641, where x 2 < 5.991 indicates that there is no significant relationship between the level of acquisition of information sources with the level of knowledge of adolescents about HIV/AIDS. The conclusion is that there is no significant relationship between the level of acquisition of information sources with the level of knowledge of adolescents about HIV/AIDS at SMK Negeri 1 Pandak Bantul.